Analysis and Kinematic Simulation of Adjustable Solar Panel Mechanism - Cui Bingyan; Chen Peng; Wu Xiaoxuan; Xie Yongtao; Xiao Shihao (Jixie chuandong)
According to the requirements of energy supply of lunar exploration engineering spacecraft， a novel adjustable solar panel with three degrees of freedom is proposed. The 2UU-UPU parallel mechanism is adopted as the prototype of adjustable solar panel mechanism. The constraint equation and positional relationship of the adjustable solar panel mechanism are analyzed， the degree of freedom of parallel robot is solved by the theory of spiral， and the positional anti-solution equation is introduced by the modified Kutzbach-Grübler formula. On this basis， the system is simulated by using Adams software， and the simulation results are compared with theoretical numerical calculations to verify the correctness of mathematical modeling of the adjustable solar panel mechanical and the rationality of the three-dimensional solid model.